MOS2 Impurities: Evidence of Native Cs Impurities and Metal–Insulator Transition in MoS2 Natural Crystals (Adv. Electron. Mater. 6/2016). (15th June 2016) - Molle, Alessandro; Fabbri, Filippo; Campi, Davide; Lamperti, Alessio; Rotunno, Enzo; Cinquanta, Eugenio; Lazzarini, Laura; Kaplan, Daniel; Swaminathan, Venkataraman; Bernasconi, Marco; Longo, Massimo; Salviati, Giancarlo
Abstract : Charged impurities in MoS2 multilayer crystals can have deep implications in the overall electronic properties. In article number 1600091, Molle and co‐workers report on the incorporation of native Cs impurities into divacancy complexes of the MoS2 structure. These defects may determine localization effects in the electronic conduction of the multilayer MoS2 that are reflected in the observation of a variable range hopping transport and a metal‐insulator transition.